Economic status, family size and educational status of the child as determinants of child labour in Ondo State, Nigeria (2010)
The study investigated the correlations among economic status, family size and the educational status of the child and child labour in Ondo state, Nigeria. Three hundred and ninety-two working children, whose ages range between 9-14 years and working across various industries (hawking, apprenticeship, 'household servants and farming) were randomly selected from three local government areas that reflect urban, semi-urban and rural settings. A guided questionnaire titled "Economic status, Family size, Educational status and Child labour" with five sections, each section measuring an aspect of the dependent and independent variables, was the main instrument used in collecting data. Findings showed that all the independent variables have relative contribution to child labour in term of their magnitude thus: economic status, β=.266, t=4.903, p < 0,05; educational status, β =.201, t=4.043, p < 0.05; family size, β =,210, t=3.652, p < 0.05. It is recommended that the advocacy role of industrial social worker in the establishment of good welfare policies, correct pricing of labour, free and compulsory education will reduce child labour yet adequate labour working force will be guaranteed in the workplace.